Implementasi Promosi Kesehatan Di UPTD Rumah Sakit Khusus Paru Provinsi Sumatera Utara Tahun 2025 - Aidha, Zuhrina; Amalona, Ridho Angga; Qur-ani, Oktafera Halmi; Melinda, Siska; Handoko, Fauziah; Paramitha, Lydia; Andwina, Andwina; Nurdilla, Niswa (Yayasan Jompa Research and Development, 2025)
This study aims to describe the implementation of Hospital Health Promotion (PKRS) at the Special Pulmonary Hospital Technical Implementation Unit of North Sumatra Province in 2025. The background of the study is based on the importance of PKRS in increasing the awareness, attitude, and healthy behavior of patients and their families, as well as supporting the achievement of public health status. The study uses a qualitative approach with observation and in-depth interviews with PKRS officers, as well as a review of hospital documents. The results of the study indicate that the implementation of PKRS has been going quite well, marked by the existence of a special PKRS unit and support from hospital management through the preparation of SOPs and regular monitoring and evaluation. Health promotion activities are carried out through individual or group counseling, as well as utilizing print, electronic, and social media. Thus, the study found several obstacles, including budget limitations, infrastructure, and patients' limited time to participate in education. The program's accessibility is considered quite good because health information can be accessed through various hospital services and social media. Overall, the PKRS at UPTD RS Khusus Paru PROVSU has been implemented according to standards, although it still requires reinforcement in terms of resources and budget support to reach a wider audience and be sustainable.